Pola kuman pada penderita Infeksi Saluran Kemihdi RSUP Dr Kariadi Semarang - Joni Karjono, Bambang; Susilaningsih, Neni; Damma Purnawati, Ratna (Jurnal Kedokteran YARSI, 2009)
Urinary Tract Infection (UTI) is one of the most common bacterial infections found in clinical practice. The incidence of UTI increases with age. Despite various causes, the main causal agent is Escherichia coli.The aim of this study is to observe the pattern of bacteria underlying UTI in Dr. Kariadi Teaching Hospital, Semarang. A cross sectional design study was conducted using urine samples collected from 195 patients being diagnosed as UTI. Urine samples were cultured and counted according to microbiology standard method. Data obtained were analyzed employing descriptive approach. The result showed that 79 individuals (40.5%) were suffering from UTI, consisting of 31.6% male and 68.4%women. Most of the UTI patients were due to E. coli (65.8%) followed by E.coli and S. aureus (10.1%), S.Aureus (8.9%), Enterobacter sp. (7.6%), E. coli and Pseudomonassp. (2.5%), Enterobacter sp.E. coli (2.5%), Enterococcus sp. (1.3%) and E.coli, S. aureus and Enterobacter sp. (1.3%). It was concluded that the most common cause of UTI was E. coli and women were more frequently affected than men.